PENGARUH KUALITAS PELAYANAN DAN PERSEPSI NILAI TERHADAP KEPUASAN KONSUMEN DALAM PEMBELIAN PRODUK BAHAN BANGUNAN PADA UD. TARU GUMANA - Meryawan, I Wayan; Fitriandari, Mahayanti; Dwi Yoga, I Gusti Ngurah (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2024)
Business competition has a significant impact on the industry, especially the fulfillment of consumer satisfaction perception which is the main problem, the weakness of the building store industry in meeting consumer satisfaction occurs in UD. Taru Gumana is caused by the low quality of service and the perception of value obtained by consumers. The purpose of this study is to determine the partial and simultaneous influence of service quality and value perception on consumer satisfaction in purchasing building material products at UD. Taru Gumana. This study is a quantitative study involving a sample of 96 respondents using the non-probalility sampling method. The data analysis technique used in this study uses hypothesis testing. The data collection technique uses questionnaire distribution. The results of the study stated that service quality and value perception had a positive and significant effect on consumer satisfaction and service quality and value perception together had a significant effect on consumer satisfaction. Furthermore, the implications of this research can build a way to increase consumer satisfaction, one of which is by paying attention to strengthening value perception so that the expectations desired by consumers can be realized and also inseparable from improving service quality.